Europejskie wyzwania regionalne a generowanie społeczeństwa obywatelskiego - Chodubski, Andrzej (Eastern Review, 2018)
The author notes that nowadays the researchers start to believe that the phenomenon of change in Europe is strongly connected with the construction and development of civil society.Achieving a civil society was one of the fundamental goals of the European Union’s founders.Today, it is still one of the most important tasks for EU supporters.It is closely related to the observance of civil rights in individual countries of the European Union, and sharing similar values by all the Union’s assets. Universal values are becoming increasingly important for EU citizens.According to the author, this has an impact on the formation of Euroregions. Euroregions mean legal and institutional cooperation between cross-border regions of individual countries.This type of cooperation is also part of the phenomenon of civil society.In the further part of the article, the author mentions factors that are indispensable for the creation of a civil society.